2018
DOI: 10.1051/matecconf/201815005032
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Psychological Capital on the Ethical Behavior of Teachers: A Case of Educational Sector in Pakistan

Abstract: This study aims at investigating the effect of psychological capital on the ethical behavior of teachers in the higher educational sector of Pakistan. This study applied quantitative approach to collect data through questionnaire based survey from the teaching staff of Rawalpindi and Islamabad region universities in Pakistan. This study used descriptive statistics and step wise regression to analyze the collected data. Results of the study indicate that psychological capital has positive and statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The influence of psychological capital on employees' innovative behavior has also been explored in the context of e-leadership, with psychological capital and affective commitment to leadership identified as mediating factors (Li & Xiao, 2023). Moreover, psychological capital has been found to have a positive and statistically significant effect on the ethical behavior of teachers in the higher educational sector (Rehman et al, 2018). In summary, the literature suggests that psychological capital plays a crucial role in influencing innovative behavior, with its mediating effects on various factors such as leadership, knowledge sharing, and ethical behavior being of particular interest.…”
Section: Discussionmentioning
confidence: 98%
“…The influence of psychological capital on employees' innovative behavior has also been explored in the context of e-leadership, with psychological capital and affective commitment to leadership identified as mediating factors (Li & Xiao, 2023). Moreover, psychological capital has been found to have a positive and statistically significant effect on the ethical behavior of teachers in the higher educational sector (Rehman et al, 2018). In summary, the literature suggests that psychological capital plays a crucial role in influencing innovative behavior, with its mediating effects on various factors such as leadership, knowledge sharing, and ethical behavior being of particular interest.…”
Section: Discussionmentioning
confidence: 98%
“…Later, the expert researchers checked the accuracy of scale and confirmed its validity. At the same time, a pilot study was conducted to evaluate the reliability of the instrument (Kain 2007 ; ur Rehman et al 2018 ) as a pilot study is usually conducted to test the reliability of scale. Some items were deleted due to its weakness and a more valid scale was operationalized after pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Few researchers have found that there was close relationship exist between ethical leadership & organizational identification and organizational citizenship behavior (Walumbwa, 2012). (Rehman, 2018) Ethical Leadership is considered as key ingredients of the organization in order to gain significant position in the corporate world. Even today the concept of ethical leadership helps the organization to gain the competitive environment in terms of innovativeness and creativity.…”
Section: Introductionmentioning
confidence: 99%